2D Titanium Carbide (MXene) Based Films: Expanding the Frontier of Functional Film Materials. (8th August 2021) - Li, Guohao; Wyatt, Brian C.; Song, Fei; Yu, Changqiang; Wu, Zhenjun; Xie, Xiuqiang; Anasori, Babak; Zhang, Nan
Abstract: 2D titanium carbide (Ti3 C2 T x ) MXene films, with their well‐defined microstructures and chemical functionality, provide a macroscale use of nano‐sized Ti3 C2 T x flakes. Ti3 C2 T x films have attractive physicochemical properties favorable for device design, such as high electrical conductivity (up to 20 000 S cm –1 ), impressive volumetric capacitance (1500 F cm –3 ), strong in‐plane mechanical strength (up to 570 MPa), and a high degree of flexibility. Here, the appealing features of Ti3 C2 T x ‐based films enabled by the layer‐to‐layer arrangement of nanosheets are reviewed. We devote attention to the key strategies for actualizing desirable characteristics in Ti3 C2 T x ‐based functional films, such as high and tunable electrical conductivity, outstanding mechanical properties, enhanced oxidation‐resistance and shelf life, hydrophilicity/hydrophobicity, adjustable porosity, and convenient processability. This review further discusses fundamental aspects and advances in the applications of Ti3 C2 T x ‐based films with a focus on illuminating the relationship between the structural features and the resulting performances for target applications. Finally, the challenges and opportunities in terms of future research, development, and applications of Ti3 C2 T x ‐based films are suggested. A comprehensive understanding of these competitive features and challenges shall provide guidelines and inspiration for the further development of Ti3 C2 T x ‐based functional films, and contribute to the advances in MXene technology. Abstract : Assembling Ti3 C2 T x nanosheets into films with well‐defined microstructures and unique surface properties creates attractive physicochemical properties favorable for device design, which has emerged as a prevailing paradigm and expanded the scopes in functional film materials. This review provides a series of optimizing strategies about the competitive features of Ti3 C2 T x ‐based films and its applications. In addition, prospects on the future development of Ti3 C2 T x ‐based films are provided.